Transedições: As duas lições de francês e inglês de Shakespeare - Taylor, Gary (Letras, 2024)
Editions translate. Translations edit. Although these principles apply to all editions and translations, they are particularly conspicuous in some transeditions, like Jerome’s Latin Bible, or Shakespeare’s Henry V. Shakespeare’s play survives in two very different versions: a quarto text published in 1600 (The Chronicle History of Henry the fift) and the posthumous 1623 folio Comedies, Histories, & Tragedies (The Life of Henry the Fift). Both texts contain a comic scene in which a French princess, with the help of her French attendant, begins to learn English. But of the 697 words of this scene in The Life, only three appear together in the same order in the same speech in The Chronicle History. Nevertheless, in both texts the scene dramatizes translation—and mistranslation. Both Katherine and Alice make comic mistakes; but both texts also contain other mistakes that cannot be plausibly attributed to the characters, seeming instead to have been introduced by compositors in the printing house or by copyists preparing the manuscripts those compositors were given. Can we distinguish the deliberate mistranslations from the accidental ones? Abridgement from expansion? Shakespeare’s own mistakes in French from the mistakes made by those who transmitted his texts? If so, how?